Pork barrel politics how government spending determines elections in a polarized era - Sidman, Andrew H. (Columbia University Press, 2019)
Andrew Sidman offers a systematic explanation for how political polarization affects the electoral influence of district-level federal spending. Pork Barrel Politics is an empirically rich account of the surprising repercussions of bringing pork home, with important consequences in our polarized era.